2003
DOI: 10.1002/uog.170
|View full text |Cite
|
Sign up to set email alerts
|

Absent nasal bone at 11–14 weeks of gestation and chromosomal defects

Abstract: Objective To examine the association between absence of the nasal bone at the 11-14-week ultrasound scan and chromosomal defects. NT < 2.5 mm, for NT ≥ 4.5 mm. In the chromosomally abnormal group the nasal bone was absent in 161/242 (66.9%) with trisomy 21, in 48/84 (57.1%) with trisomy 18, in 7/22 (31.8%) Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 9 publications
2
82
0
5
Order By: Relevance
“…[8][9][10] Using firsttrimester sonography, Prefumo et al 11 showed a trend of a higher incidence of an absent nasal bone in fetuses of healthy Asian mothers. Another study by Cicero et al 12 reported that the incidence of an absent nasal bone at 11 to 14 weeks' gestation was substantially higher in African Caribbean (10.4%) and Asian (6.8%) fetuses than in white fetuses (2.8%).…”
mentioning
confidence: 99%
“…[8][9][10] Using firsttrimester sonography, Prefumo et al 11 showed a trend of a higher incidence of an absent nasal bone in fetuses of healthy Asian mothers. Another study by Cicero et al 12 reported that the incidence of an absent nasal bone at 11 to 14 weeks' gestation was substantially higher in African Caribbean (10.4%) and Asian (6.8%) fetuses than in white fetuses (2.8%).…”
mentioning
confidence: 99%
“…For this purpose, ultrasound has proved to be an invaluable diagnostic and screening tool. The absence of the fetal nasal bone on prenatal sonogra-phy between 11 and 14 weeks' gestation has been suggested by some, 5,6 but not all, 7 as a useful screening tool for detection of trisomy 21. Nasal bone hypoplasia during the second trimester has also been associated with a high risk for trisomy 21 and has been suggested as a highly sensitive and specific sonographic marker for chromosomal aneuploidy.…”
mentioning
confidence: 99%
“…Several studies have demonstrated a strong between an absent nasal bone at 11-14 weeks of gestation and trisomy 21 [32][33][34]. And in the combined data from these studies, the fetal nasal bone was absence in 69% of fetus with trisomy 21 [26].…”
Section: Discussionmentioning
confidence: 68%
“…In present study, the fetal structural defects of Down syndrome were poverty in anatomical ultrasound scanning at the 18-22 weeks of gestation, so an association with many approaches was useful to improve the detection rate of trisomy 21. Because the absence of the nasal bone is not related to fetal NT thickness [31], and the finding screening of maternal age alone showed no advantage for detection of trisomy 21 [13], therefore, they could be combined relatively simply to provide a more effective method of early screening for trisomy 21 [6,33].…”
Section: Discussionmentioning
confidence: 99%